Learning Outcomes in Calculating the Qibla Direction Using Spherical Triangles in Law Class - Solikin, Agus; Naufal, Faiz Muhammad; Nafan, Abdul Wahab (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This article aims to analyse the learning outcomes in calculating the qibla direction using the cosine and sine formulas of spherical triangles in the Constitutional Law class of the Faculty of Sharia and Law at UIN Sunan Ampel Surabaya during the odd semester of the 2024/2025 academic year. This research employs a mixed-method approach, combining descriptive quantitative and qualitative methods through a case study conducted in the Law class. Data collection was conducted using a questionnaire with a dichotomous scale. The collected data includes information before and after the lecture on calculating the qibla direction, which utilises the cosine and sine formulas of spherical triangles. Furthermore, changes in data before and after the lecture are analysed based on the level of change in the responses to the questionnaires completed by students. Based on the results of the analysis conducted, it was found that many students lacked comprehensive knowledge about the direction of the qibla before the lectures, both from a fiqh and a mathematical perspective. Following the lectures, a significant change occurred in the understanding of this qibla direction, which, mathematically, increased by 65.77%. Meanwhile, in terms of calculation skills for determining the qibla direction, before the lectures were held, only a small fraction of the students stated they could calculate the qibla direction for both areas in Indonesia and outside Indonesia. After the lectures, there was a significant change of 74.32% expressing their ability to calculate the qibla direction for areas in Indonesia, as well as outside Indonesia.